Urban planning following humanitarian crises: supporting urban communities and local governments to take the lead. (April 2018) - Maynard, Victoria; Parker, Elizabeth; Yoseph-Paulus, Rahayu; Garcia, David
This paper describes research investigating UN-Habitat's experience supporting communities and local government to undertake urban planning following humanitarian crises. Two case studies were examined: Banda Aceh, Indonesia, following the Indian Ocean earthquake and tsunami in 2004; and Tacloban, the Philippines, following Super Typhoon Haiyan in 2013. The study found that urban planning following humanitarian crises can empower communities and governments to manage their own recovery. However, they may lack the knowledge, experience, time, tools or technology needed to take the lead. Organizations supporting urban communities and local government to undertake urban planning following humanitarian crises should consider: the most appropriate speed, scale and depth of the intervention given the context and their own funding and capacity; building local government capacity through secondments or partnerships; establishing a recovery and reconstruction planning task force; appropriate strategies for working with affected communities and their leaders; and advocating for national government support.